Enantioselective synthesis of (-)-pinellic acid - Naidu, S. Vasudeva; Kumar, Pradeep (Tetrahedron Letter, 2007)
An enantioselective convergent approach toward the total synthesis of pinellic acid 1 from 1,9-nonanediol is described. The synthetic strategy features iterative Sharpless asymmetric dihydroxylation, Sonogashira coupling and Birch reduction. (c) 2007 Elsevier Ltd. All rights reserved.

Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis